A novel allele of ASY3 is associated with greater meiotic stability in autotetraploid Arabidopsis lyrata - Seear, Paul J; France, Martin G; Gregory, Catherine L; Heavens, Darren; Schmickl, Roswitha; Yant, Levi; Higgins, James D (PLoS genetics, 2020)
In this study we performed a genotype-phenotype association analysis of meiotic stability in 10 autotetraploid Arabidopsis lyrata and A. lyrata/A. arenosa hybrid populations collected from the Wachau region and East Austrian Forealps. The aim was to determine the effect of eight meiosis genes under extreme selection upon adaptation to whole genome duplication. Individual plants were genotyped by high-throughput sequencing of the eight meiosis genes (ASY1, ASY3, PDS5b, PRD3, REC8, SMC3, ZYP1a/b) implicated in synaptonemal complex formation and phenotyped by assessing meiotic metaphase I chromosome configurations. Our results reveal that meiotic stability varied greatly (20-100%) between individual tetraploid plants and associated with segregation of a novel ASYNAPSIS3 (ASY3) allele derived from A. lyrata. The ASY3 allele that associates with meiotic stability possesses a putative in-frame tandem duplication (TD) of a serine-rich region upstream of the coiled-coil domain that appears to have arisen at sites of DNA microhomology. The frequency of multivalents observed in plants homozygous for the ASY3 TD haplotype was significantly lower than in plants heterozygous for ASY3 TD/ND (non-duplicated) haplotypes. The chiasma distribution was significantly altered in the stable plants compared to the unstable plants with a shift from proximal and interstitial to predominantly distal locations. The number of HEI10 foci at pachytene that mark class I crossovers was significantly reduced in a plant homozygous for ASY3 TD compared to a plant heterozygous for ASY3 ND/TD. Fifty-eight alleles of the 8 meiosis genes were identified from the 10 populations analysed, demonstrating dynamic population variability at these loci. Widespread chimerism between alleles originating from A. lyrata/A. arenosa and diploid/tetraploids indicates that this group of rapidly evolving genes may provide precise adaptive control over meiotic recombination in the tetraploids, the very process that gave rise to them.
Keywords: proteiny huseníčku; Chromosomal Proteins, Non-Histone; Arabidopsis; Chromosome Pairing; párování chromozomů; Arabidopsis Proteins; Meiosis; DNA vazebné proteiny; chromozomy rostlin; Chromosomes, Plant; meióza; segregace chromozomů; tetraploidie; Diploidy; chromozomální proteiny, nehistonové; Chromosome Segregation; Alleles; Tetraploidy; diploidie; alely; DNA-Binding Proteins